Leachability and strength of kaolin stabilized with cement and rubber - Ho, Meei-Hoan; Tarmizi, Ahmad; Chan, Chee-Ming; Bakar, Ismail (International Journal of Sustainable Construction Engineering and Technology, 2011)
Yearly, the disposal of used tyres is a major environmental problem for countries all over the world. This causes environmental hazards such as uncontrolled fire, consume landfill space, breeding ground for mosquitoes and contaminating the soil and vegetation. Hence, urgent steps were identified to produce new methods of recycling the waste tyres to solve this hazard. This study reviews the feasibility of using waste tyres in the form of rubber chips with cement to stabilize soft clay and the effect to the environment. The focus of this study was mainly the strength and leachability characteristics of kaolin as base clay, admixed with cement as the binder and rubber chips as an additive. Leaching test is used to evaluate the performance of cementitious materials for stabilization and solidification (S & S) of hazardous materials such as waste or contaminated soil. In this study, cylindrical stabilized clay specimens were prepared with various rubber chips contents and cement, and then aged for 28 days. Cylindrical specimens were then subjected to unconfined compressive strength test (using Geocomp LoadTrac II) and the specimens were later dried in oven at 105° before tested for leaching tests. These leaching methods are Acid Neutralization Capacity Test (ANC) and Synthetic Precipitation Leaching Procedure (SPLP). The solidified samples were checked on six different heavy metals, namely copper, chromium, cadmium, arsenic, zinc and plumbum. Analysis was carried out by relating the effects of 0, 2 or 4 % cement as well as 0, 5, 10 and 15 % rubber chips addition to the base clay and its leachability. As observed, the curing of specimen for 28 days was in a range of 66.24 to 249.4 kPa. Specimen with 4 % cement is able to produce ANC9 of about 0.13 meq HNO3/g specimen. However specimen with 0 % and 2 % cement for different rubberchips content shows that the specimen do not have the capacity to neutralize acid at pH 9. Therefore, more cement (> 4 %) is needed to achieve ANC9. SPLP results showed that all six different heavy metals tested do not exceed the approved limit for drinking water by World Health Organization (WHO), United States Environmental Protection Agency (USEPA) and Ministry of Health in Malaysia.